2006
DOI: 10.1111/j.1420-9101.2005.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Ornaments or offspring? Female sticklebacks (Gasterosteus aculeatus L.) trade off carotenoids between spines and eggs

Abstract: Hypotheses and models to explain female ornaments often assume that the elaborated traits are condition dependent; nevertheless, few empirical studies have addressed this topic. We studied a population of three‐spined sticklebacks (Gasterosteus aculeatus) in which the females have conspicuous, carotenoid‐based red coloration to their pelvic spines. The red coloration seems not to be condition dependent, as coloration is negatively associated with age and body length and not associated with condition. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 59 publications
2
60
2
Order By: Relevance
“…Similar spawning color selection would likely affect males and females differently because males have no alternative use for their carotenoids while females must partition their carotenoids between themselves and their young (Craig and Foote 2001;Foote et al 2004;Nordeide et al 2006). Our data are consistent with this apparent trade-off between body and egg color in female sockeye salmon (Crozier 1970;Craig and Foote 2001;Foote et al 2004).…”
Section: Significance Of Snout Lengthsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar spawning color selection would likely affect males and females differently because males have no alternative use for their carotenoids while females must partition their carotenoids between themselves and their young (Craig and Foote 2001;Foote et al 2004;Nordeide et al 2006). Our data are consistent with this apparent trade-off between body and egg color in female sockeye salmon (Crozier 1970;Craig and Foote 2001;Foote et al 2004).…”
Section: Significance Of Snout Lengthsupporting
confidence: 90%
“…It is also important to provision eggs with carotenoids to improve the immune response and survival of young (Blount et al 2000(Blount et al , 2002Tyndale et al 2008). Many organisms concentrate carotenoids in their eggs at the expense of their own body color and, potentially, effective immune response (Green 1965;Skarstein and Folstad 1996;Royle et al 2003;Nordeide et al 2006;Baeta et al 2008).…”
Section: Significance Of Snout Lengthmentioning
confidence: 99%
“…A possible physiological basis for our finding about the negative relationship between female redness and the early viability of her offspring could be that the development of carotenoid-based breeding coloration in females might reduce the availability of these valuable pigments (antioxidants) to developing embryos, thus leading to lower incubation success per brood (see e.g., Ahmadi et al 2006;Tyndale et al 2008). In support of this idea, Nordeide et al (2006Nordeide et al ( , 2008 found that the intensity of red ornamental coloration in both the stickleback and Arctic charr females may, indeed, be negatively correlated with the amount of carotenoids in the eggs, though the relationship was only marginally significant in the latter case.…”
Section: Discussionmentioning
confidence: 66%
“…By experimentally controlling for the confounding maternal and environmental effects (Sheldon 2000), it was possible to test whether differently coloured males differ in their genetic quality, determined as their offspring's early survival and growth performance. On the other hand, because maternal effects are known to be pronounced in early developmental phases of fish (see Kamler 2008 and references therein), and because charr females might be constrained to trade-off carotenoids between investment in ornamentation and investment in eggs (Nordeide et al 2006(Nordeide et al , 2008, we also examined whether there are any correlative evidence that the variation in sexual coloration among females (dams) would be related to their reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…competitive traits : ornaments, armaments, aggression, etc. (Cain & Ketterson, 2012; West-Eberhard, 1983)) is often associated with decreased maternal effort (Bell et al, 2011; Dantzer et al, 2011; Fite et al, 2005; Fitzpatrick et al, 1995; Nordeide et al, 2006; Packer et al, 1995; Rosvall, 2011). …”
Section: Introductionmentioning
confidence: 99%